Konsep Ulil Albab Dalam Al-Qur'an: Menantang Model Pendidikan Dogmatis di Madura Melalui Pendekatan Tafsir Kontekstual Di Tingkat Pendidikan Dasar - Samsul Arifin (LP2M Institut Agama Islam Nazhatut Thullab Sampang, 2026)
This research examines the paradox between the ideal concept of Ulil Albab in the Qur'an and the reality of Islamic educational practices in Madura, which tend to be dogmatic. The Qur'an consistently glorifies the profile of Ulil Albab as individuals capable of integrating dhikr (spiritual depth) and fikr (intellectual acuity). However, the dominant educational model, particularly within traditional salaf pesantren, often prioritizes obedience and memorization over critical reasoning, potentially hindering the emergence of a generation with these characteristics. This research employs a qualitative approach with a library research method to analyze this issue. The findings indicate that the revitalization of the Ulil Albab concept through Abdullah Saeed's contextual interpretation (tafsir) can serve as a philosophical foundation for educational reform. Furthermore, this article proposes the Contextual Teaching and Learning (CTL) model as a pedagogical framework to translate the values of Ulil Albab into learning practices at the elementary level. In conclusion, the synergy between contextual interpretation as a methodology for meaning-making and CTL as a learning strategy can create an educational ecosystem that fosters critical reasoning, creativity, and spiritual awareness in a balanced manner, offering a solution to move beyond dogmatism towards enlightenment.